Venous thromboembolism in patients undergoing pancreatic cancer surgery (PaTR-VTE) with curative intent; protocol of a prospective observational study - Maria P. Ntalouka; Dimitrios Symeonidis; Paraskevi Kotsi; Efthymia Petinaki; Miltiadis Matsagkas; Konstantinos Tepetes; Dimitrios Zacharoulis; Eleni M. Arnaoutoglou (BMC Surgery)
Abstract Background Pancreatic cancer is probably the most thrombotic malignancy, with an incidence of venous thromboembolism (VTE) of up to 18%. However, the exact pathophysiological mechanisms involved in the development of VTE in the setting of pancreatic cancer are not yet well understood. The primary endpoint of the study is to evaluate the neutrophil/lymphocyte ratio (NLR) and other coagulation biomarkers as predictors of VTE in patients with pancreatic cancer undergoing surgery with curative intent. The exact incidence of VTE, perioperative coagulation status of patients and the possible determinants of VTE in the aforementioned population are the secondary study objectives. Methods This prospective, non-interventional observational study is conducted according to the STROBE concept. It has been approved by the ethical committee and registered (NCT05964621) and will include eligible patients with primary pancreatic cancer with resectable or borderline resectable disease undergoing surgery with curative intent. Exclusion criteria are: Refusal to participate, previous thromboembolic event < 6 months, ASA score > 3, patients deemed inoperable intraoperatively and the concurrent presence of a second primary malignancy. Three blood samples are taken from all patients (preoperatively, immediately after the operation, and before discharge) and the serum values of the following parameters are determined: Haemoglobin, white blood cells, INR, liver and kidney function tests, von Willebrand factor, factors VIII and XI, D-dimers, fibrinogen, platelet function, Adamts 13 and anti-Xa. One month after the procedure, scheduled screening for asymptomatic deep vein thrombosis (DVT) is performed with a lower extremity ultrasound triplex study. In addition, thromboembolic events (DVT, pulmonary embolism (PE)) diagnosed during the hospital stay period are recorded. Low molecular weight heparin will be routinely administered from the first postoperative day, with the dosage, i.e. prophylactic or therapeutic titrated according to the patient’s history of cardiovascular disease. According to the literature, the pooled specificity of the admission NLR for 30-day VTE and PE prediction is 80.5%, while the VTE rates after pancreatectomy is 1.5%. Based on a 95% confidence level and a precision of 0.1, the estimated sample size for the specificity outcome is 62 patients. Discussion The aim of this study is to identify predictors of postoperative VTE in patients undergoing pancreatic cancer surgery. The results could lead to an optimization of perioperative care. Trial registration NCT05964621. Registered on July, 2023 clinicaltrials.org.